(untitled) (Revista Iberoamericana de Bioética, 2020)
Although science and biotechnoscience are meant to protect lives, they can also pose risks to survival. We fear them at the same time that we reap their benefits, possibly because here in Brazil and all over the world we are living through a sombre period assailed by the uncertainties of “the biopolitics of death”, or what we call “necropolitics”. This paper performs a critical review of the current literature in an attempt to reflect on the relationship between science, biotechnoscience, biopolitics and bioethics. This will hopefully contribute to a clear perception of the effects of a “science without conscience”, and of the need to build biotechnoscience in response to social demands in times of COVID-19.